2014
DOI: 10.1539/joh.13-0256-ra
|View full text |Cite
|
Sign up to set email alerts
|

High‐altitude Pulmonary Edema: Review

Abstract: High‐altitude Pulmonary Edema: Review: Shuchi BHAGI, et al. Defence Institute of Physiology and Allied Sciences (DIPAS), Defence Research and Development Organization (DRDO), India— Objective At High altitude (HA) (elevation >2,500 m), hypobaric hypoxia may lead to the development of symptoms associated with low oxygen pressure in many sojourners. High‐altitude pulmonary edema (HAPE) is a potentially fatal condition, occurring at altitudes greater than 3,000 m and affecting rapidly ascending, non‐acclimatized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 73 publications
(91 reference statements)
2
42
0
3
Order By: Relevance
“…However, while increasing oxygen concentrations in hypobaric environments mediates stress in plants, the data presented here suggest that exposing plants to at least mild hypobaric conditions can also serve to mediate plant stress in low oxygen environments. Interestingly, although the importance of oxygen in human hypobaric stress, such as the high-altitude pulmonary edema common to extreme mountain climbers, has long been appreciated (Hackett and Roach, 1987), it is becoming increasingly clear that the combination of stresses associated with hypobaric environments elicits complex physiological responses, and requires complex mediation (Bhagi et al, 2014). The establishment of protected agriculture in extreme environments—whether on the surface of Mars, in exploration vehicles, or for terrestrial applications—will require careful management of in situ resources and engineering considerations to optimize the internal environment for plant health and productivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, while increasing oxygen concentrations in hypobaric environments mediates stress in plants, the data presented here suggest that exposing plants to at least mild hypobaric conditions can also serve to mediate plant stress in low oxygen environments. Interestingly, although the importance of oxygen in human hypobaric stress, such as the high-altitude pulmonary edema common to extreme mountain climbers, has long been appreciated (Hackett and Roach, 1987), it is becoming increasingly clear that the combination of stresses associated with hypobaric environments elicits complex physiological responses, and requires complex mediation (Bhagi et al, 2014). The establishment of protected agriculture in extreme environments—whether on the surface of Mars, in exploration vehicles, or for terrestrial applications—will require careful management of in situ resources and engineering considerations to optimize the internal environment for plant health and productivity.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review identified a number of possible gene mutations that may be linked to the pathogenesis and development of HAPE -many are downstream targets of HIF-1α and also involved in either HPV or HVR. These include the angiotensin-1 converting enzyme (ACE), vascular endothelial growth factor (VEGF), tyrosine hydroxylase (TH), serotonin transporter (5HTT), endothelin 1 (EDN1) and endothelial nitric oxide synthase (eNOS) genes (29). HAPE has also recently been associated with an overactive sympathetic nervous system, (30) the major-histocompatibility complex, (31) an increase in hepcidin levels (32) as well as lack of oestrogen (33).…”
Section: Risk Factorsmentioning
confidence: 99%
“…8 Although sildenafil and tadalafil as well as newer anti-PHT drugs promote pulmonary vasodilation, further studies are needed to demonstrate their efficacy in HAPE treatment. 35 Chronic High-altitude Illness: Chronic Mountain Sickness CMS, also known as Monge disease, is a clinical syndrome occurring in natives or long-term residents above 2500 m. Characteristics of this disease includes severe hypoxemia with excessive erythropoiesis, which can lead to moderate or severe PHT with cor pulmonale. An international consensus statement of the International Society for Mountain Medicine summarized the clinical picture of CMS.…”
Section: High-altitude Illnessmentioning
confidence: 99%